Evaluation of 222Rn and 226Ra concentrations in cement and limestone of Sheikh Buddin Hill, Pezu, Pakistan using different techniques - Ahmad, Nisar; Nasir, Tabassum; Rizwan, Sohail; Ullah, Hamid; Bakhsh, Muhammad (Taylor & Francis, 2019)
Lucky Cement Factory, Pezu is using limestone of Sheikh Buddin Hills as a raw material in cement. Workers of the factory have direct and general public have indirect exposure to radiological hazard due to natural radionuclides present in limestone. To address the radiological hazards, limestone, mixed (limestone+clay) and cement samples were evaluate for concentrations of 222Rn and 226Ra using CR-39, RAD7 and HPGe detectors. Maximum mean values of 222Rn using CR-39 and RAD7 detectors were found 1447 ± 198 and 1416 ± 74 Bq.m−3 in cement samples and minimum were found in 536 ± 122 and 525 ± 45 Bq.m−3 limestone samples, respectively. Maximum mean value of radon exhalation rate of 12.28 ± 1.68 Bq.m−2 h−1 in cement samples was found below the world average value of 57.6 Bq.m−2 h−1. Maximum mean values of 226Ra measured by CR-39 and HPGe detectors were found 24.25 ± 3.35 and 23.6 ± 0.70 Bq.kg−1 in cement samples and minimum were found in 8.98 ± 2.02 and 9.19 ± 0.40 Bq.kg−1 limestone samples, respectively. A positive correlations (R2 = 0.9714) using CR-39 and RAD7 detectors and (R2 = 0.9573) using CR-39 and HPGe detectors were obtained for the concentrations of 222Rn and 226Ra, respectively. Maximum mean value of annual effective dose of 347.78 ± 47.58 µSv.y−1 in cement samples was found below the world average value of 1100 µSv.y−1. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.